2021
DOI: 10.1093/cid/ciab546
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Current Opioid Agonist Therapy on Hepatitis C Virus Treatment Initiation Among People Who Use Drugs From the Direct-acting Antiviral (DAA) Era: A Population-Based Study

Abstract: Background Evidence that opioid agonist therapy (OAT) is associated with increased odds of hepatitis C virus (HCV) treatment initiation among people who use drugs (PWUD) is emerging. The objective of this study was to determine the association between current OAT and HCV treatment initiation among PWUD in a population-level linked administrative dataset. Methods The British Columbia (BC) Hepatitis Testers Cohort was used for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 33 publications
2
9
0
Order By: Relevance
“…Our qualitative data suggest that an HCV cure fosters self-confidence, promoting overall well-being . Our observation of significant decreases in illicit drug use among HCV-cured participants is consistent with prior studies that showed improved HCV and opioid use disorder treatment outcomes with simultaneous treatment of both entities . Although desired, physical integration of medical and behavioral therapy has been difficult to achieve; OTP-integrated facilitated telemedicine appears to integrate HCV and opioid use disorder care with improved convenience, accessibility, and flexibility.…”
Section: Discussionsupporting
confidence: 81%
“…Our qualitative data suggest that an HCV cure fosters self-confidence, promoting overall well-being . Our observation of significant decreases in illicit drug use among HCV-cured participants is consistent with prior studies that showed improved HCV and opioid use disorder treatment outcomes with simultaneous treatment of both entities . Although desired, physical integration of medical and behavioral therapy has been difficult to achieve; OTP-integrated facilitated telemedicine appears to integrate HCV and opioid use disorder care with improved convenience, accessibility, and flexibility.…”
Section: Discussionsupporting
confidence: 81%
“…As OAT prescription is monthly in France, 20% of the time corresponds to two or more OAT prescriptions in the previous six The second important result is that only 15% of PWUD with chronic HCV infection in our study received DAA treatment between 2014 and 2016, suggesting that treating strategies were suboptimal in this population. Our results are consistent with previous studies conducted in other countries which have already highlighted that OAT access is a major predictor of DAA uptake [11,20,21]. Interestingly, women, as demonstrated elsewhere [15], had fewer opportunities to initiate DAA despite tending to be more adherent to OAT.…”
Section: Discussionsupporting
confidence: 92%
“…OAT effectively reduces cravings and withdrawal symptoms enabling patients to achieve physical, mental and emotional stability 9. Prolonged and sustained engagement with OAT is associated with a reduced likelihood of overdoses, mortality and infections such as hepatitis C virus (HCV) and HIV 12–14. Consequently, OAT is associated with lowered healthcare costs and improved overall quality of life 9 15 16.…”
Section: Introductionmentioning
confidence: 99%